The Analysis of Factors Related to the Company Performance with Capital Structure as an Intervening Variable in the Transportation Industry in Indonesia - Maswani Maswani; Dimas Angga Negoro; Tantri Yanuar Rahmat Syah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to examine the direct effect of the relationship between asset structure, growth, company size and business risk on the capital structure of transportation companies, as well as the indirect effect of asset structure, growth, company size and business risk on company performance through capital structure as an intervening variable. Population are companies in the Transportation industry listed on the Indonesia Stock Exchange (IDX) in 2015-2019. From this population, 145 samples from 29 transportation companies were selected as the target population, all of which became the research sample. The research method used is panel data regression. The test results reveal that the asset structure, growth and company size have a positive effect on the capital structure of the Transportation sub-sector companies listed on the IDX for the 2015-2019 period. Meanwhile, business risk does not have a positive influence on the capital structure of transportation sub-sector companies listed on the Indonesia Stock Exchange for the 2015-2019 period. In addition, in this study, the variables of asset structure, growth, business risk were positively related to the company's performance, while the variable of company size had no positive effect on the company's performance. Furthermore, the capital structure variable has a positive effect on company performance, the capital structure variable as an intervening variable explains that capital structure has no effect in intervening between growth and company business risk on company performance. While the asset structure variable and company size on company performance with capital structure as an intervening variable explains that capital structure has a significant effect in intervening between asset structure, company size and financial performance in transportation companies listed on the Indonesia Stock Exchange for the 2015-2019 period.